Judaism in the New Testament : practices and beliefs - Chilton, Bruce; Neusner, Jacob (London : Routledge, 1995)
"Judaism in the New Testament explains how the books of the early church emerged from communities which defined themselves in Judaic terms even as they professed faith in Christ. The earliest Christians set forth the Torah as they understood it - they did not think of their religion as Christianity, but as Judaism. For the first time, in Judaism in the New Testament, two distinguished scholars take the earliest Christians at their word and ask: "If Christianity is (a) Judaism, then how should we read the New Testament?" The Gospels, Paul's Letters, and the Letter to the Hebrews are interpreted to define what Chilton and Neusner call "Christianity's Judaism." Seen in this way, the New Testament will never be the same.
Judaism in the New Testament or the New Testament 's particular Judaism-- No Orthodox, traditional Judaism-- Analyzing a Judaism-- Theory of the social entity-- Paul's competitors, Jesus disciples, and the Israel of Jesus-- Practice, Jesus and the Torah-- The transformation of Judaism, from the salvation to sanctification
Includes bibliographical references and index.
Keywords: Bible. New Testament -- Criticism, interpretation, etc; Judaism (Christian theology); Christianity -- Origin; Jewish sects -- History; Judaism -- Relations -- Christianity; Christianity and other religions -- Judaism